Distance learning training in genetics and genomics testing for Italian health professionals: results of a pre and post-test evaluation (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundProgressive advances in technologies for DNA sequencing and decreasing costs are allowing an easier diffusion of genetic and genomic tests. Physicians’ knowledge and confidence on the topic is often low and not suitable for manage this challenge. Tailored educational programs are required to reach a more and more appropriate use of genetic technologies.MethodsA distance learning course has been created by experts from different Italian medical associations with the support of the Italian Ministry of Health. The course was directed to professional figures involved in prescription and interpretation of genetic tests. A pretest-post-test study design was used to assess knowledge improvement. We analyzed the proportion of correct answers for each question pre and post-test, as well as the mean score difference stratified by gender, age, professional status and medical specialty.ResultsWe reported an improvement in the proportion of correct answers for 12 over 15 questions of the test. The overall mean score to the questions significantly increased in the post-test, from 9.44 to 12.49 (p-value < 0.0001). In the stratified analysis we reported an improvement in the knowledge of all the groups except for geneticists; the pre-course mean score of this group was already very high and did not improve significantly.ConclusionDistance learning is effective in improving the level of genetic knowledge. In the future, it will be useful to analyze which specialists have more advantage from genetic education, in order to plan more tailored education for medical professionals.